STRATEGI PEMASARAN TOKO PAKAIAN MUSLIM MENGHADAPI PERSAINGAN BISNIS DI KOTA KENDARI (STUDI KASUS TOKO NAZWA HIJAB) - Makmur, Muhammad Rizaldi; Alimusa, La Ode; Hamid, Nisrina; Rosniatin, Rosniatin (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2024)
Study aims to understand marketing strategies in facing business competition, the challenges encountered, and solutions in facing marketing challenges for Muslim clothing at Nazwa Hijab Store. The data collection method used in this research is through observation and interviews with informants. After collecting the data, it is then analyzed using SWOT analysis. Based on the results of the data analysis conducted, it can be concluded that (1) the marketing strategy implemented by Nazwa Hijab Store in facing business competition includes maintaining the quality and standards of its products, following clothing trends, setting prices according to product quality and affordability, and being located in strategic locations. (2) The challenges faced by Nazwa Hijab Store in marketing its products include a shortage of employees, delayed product deliveries, fluctuating trends, an unstable economy, and easily replicable business strategies. (3) The solutions proposed by Nazwa Hijab Store to address marketing challenges include maintaining product quality, improving service quality, prioritizing customer satisfaction and comfort, setting pricing strategies, and refining marketing strategies while enhancing the quality of customer service.